Nirmatrelvir/ritonavir for patients with SARS-CoV-2 infection and impaired kidney function during the Omicron surge - Yan, Jiayi; Cai, Hong; Wang, Jieying; Zhu, Mingli; Li, Ping; Li, Peiying; Wu, Bin; Che, Xiajing; Gu, Leyi; Mou, Shan (Frontiers in Pharmacology, 2023)
Background: Nirmatrelvir/ritonavir has demonstrated effectiveness in high-risk patients with coronavirus disease 2019 (COVID-19). However, investigations on the efficacy and safety of nirmatrelvir/ritonavir in patients with kidney dysfunction are limited. Methods: Data were collected from the patients admitted to a COVID-19 referral center in Shanghai, China. Patients were at least 18 years of age and had a baseline estimated glomerular filtration rate (eGFR) of < 60ml/min/1·73m2. The primary endpoint was a composite of all-cause mortality, intensive care unit admission, or cardiovascular events. The secondary endpoint was viral shedding. Results: Among the 195 participants, 73 received nirmatrelvir/ritonavir. A lower risk of the primary endpoint was observed in nirmatrelvir/ritonavir recipients compared with non-recipients (adjusted HR 0·56 [95%CI: 0·32-0·96]; p=0·035). Nirmatrelvir/ritonavir recipients experienced a shorter duration of viral shedding (adjusted HR 3·70 [95%CI: 2·60-5·28]; p<0·001) and faster viral load clearance versus non-recipients. Among the nirmatrelvir/ritonavir users, earlier initiation of nirmatrelvir/ritonavir within five days since COVID-19 diagnosis was related with shorter viral shedding time (adjusted HR 7·84 [95%CI: 3·28-18·76]; p<0·001) compared to late initiation. No patients reported serious adverse events during treatment. Conclusions: Our findings support the early initiation of nirmatrelvir/ritonavir for high-risk patients with impaired kidney function. This could improve patient outcomes and shorten the viral shedding period.